Marine Debris Composition and Abundance: A Case Study of Selected Coastlines in Ujong Karang, Meulaboh, West Aceh - Lisdayanti, Eka; Marlian, Neneng; Wahyuni, Sri; Najmi, Nurul; Rahmawati, Rahmawati (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Marine debris has become an increasing environmental threat in the world. West Aceh's coast is designated for tourism and fishing activities. This study determines the composition, characteristics, and abundance of waste on two selected beaches with economic activities for fishing (daily activities of coastal communities) and tourism activities. Garbage collection was carried out on two beaches on the coast of Johan Pahlawan District, West Aceh Regency, namely Pasar Baro Beach and Ujung Karang Beach. Pasar Baro Beach and Ujung Karang Beach were chosen because they are near fish market activities and recreational beaches, respectively. Determination of the sampling area by distance, from the low tide line to the first vegetation or concrete on the beach. The sampling length was measured using a 100 m roll meter parallel to the coastline. The results showed that the total weight (%) and frequency of waste per category were highest in the household category at Pasar Baro Beach. While at Ujung Karang Beach, the highest frequency of garbage is found in the variety of plastic drink bottles. The difference in abundance at the two stations is due to differences in visits and activities of the surrounding community. In addition, due to the lack of local cleaning efforts and facilities that could be more optimal, piles of garbage are still found along the coast